(untitled) (Международный научный журнал «Инженер», 2026)
This article examines the structural reliability and cyber resilience of IP-based rapid technological communication networks in railway sections, particularly using train dispatcher communication systems as an example. A logical-functional model was developed for multiple stations, demonstrating that the overall reliability of the rapid technological communication network directly depends on the coordinated operation of all its elements. Simulation experiments conducted in the MATLAB environment revealed that DoS (Denial of Service) attacks can significantly reduce network performance, increasing packet loss threefold and latency fivefold. To address these issues, scientific and technical solutions such as traffic encryption, strengthening QoS mechanisms, implementing real-time monitoring systems, optimizing resources, and using firewalls were proposed. Practical implementation of these measures improved the readiness coefficient of the rapid technological communication network, ensured compliance with international information security standards, and strengthened both the safety and stability of train traffic in railway sections.